Global Trends and Evolution of Ecotechnology in Textile Wastewater Treatment: 21-Year Bibliometric Analysis - Fifia zulti; Dyah Iswantini; Anas Miftah Fauzi; Dewi Sondari (BRIN Publishing, 2025)
The textile industry supports the global economy, but it produces dye-rich wastewater that poses a threat to ecosystems and human health. Conventional treatment methods are expensive, energy-demanding, and often unsustainable. This study examines global research trends in the application of ecotechnology for textile wastewater treatment from 2004 to 2024. Data were collected from Scopus on August 9, 2025, and analyzed using the PRISMA, Excel, and VOSviewer tools. A total of 413 peer-reviewed English papers were reviewed based on the keywords “ecotechnology” and “textile wastewater treatment.” Research output has grown significantly since 2016, driven primarily by India and China. Core topics include constructed wetlands, adsorption, and phytoremediation, while recent studies highlight advanced materials, photocatalysis, nutrient recovery, and water conservation. These developments show a shift toward hybrid systems and circular economy models. Most papers appear in multidisciplinary journals, reflecting the broad and interconnected nature of the field. Yet, significant gaps remain in linking technology with social, policy, and behavioral aspects. Stronger collaboration across disciplines is needed to connect innovation, governance, and local engagement. Such efforts will help make ecotechnology a more sustainable and scalable solution for managing textile wastewater.